Баймер: роман / Юрий Никитин - Никитин Юрий Александрович (Эксмо, 2004)
Цикл: Грядущие романы Экземпляры: ЦБ (20210511) / Инвентарный номер: 53719 / Цена: 150.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44